The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.13045/jar.2019.00185
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Acupuncture Treatment for Primary Headache Disorders in Korea

Abstract: This study was performed to review clinical research studies involving acupuncture treatment for primary headache disorders to provide a basic reference for future studies. Clinical studies of primary headache disorders treated with acupuncture were retrieved from 3 Korean electronic databases (NDSL, OASIS, and RISS). The studies were classified by year of publication, type of study, type of acupuncture, outlined acupoints, methods used for filiform needles, pharmacopuncture, auricular acupuncture, and thread-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The ear lobe auricular points (AT, LO, Eye1, Eye2) are associated with the head and face, while the upper part of the auricular region, including scapha and superior antihelix crus, correspond to the extremities (SF, AH) (Figure 3). The basic auricular sites for headaches are Shen Men, gallbladder, liver and spleen, heart, antitragus (AT1 = forehead; AT2 = temple; AT3 = occiput), 24,25 and gallbladderthree located at the ear lobe (Figure 3). 27 The utilization of functional magnetic resonance imaging (fMRI), as employed by Romoli et al to investigate brain stem auricular acupoint (BSAA), has demonstrated the potential to investigate other auricular points on the outer ear, such as the tragus, antitragus, and ear lobe.…”
Section: Evaluation Of Dp From the Perspective Of The Chinese Auricul...mentioning
confidence: 99%
“…The ear lobe auricular points (AT, LO, Eye1, Eye2) are associated with the head and face, while the upper part of the auricular region, including scapha and superior antihelix crus, correspond to the extremities (SF, AH) (Figure 3). The basic auricular sites for headaches are Shen Men, gallbladder, liver and spleen, heart, antitragus (AT1 = forehead; AT2 = temple; AT3 = occiput), 24,25 and gallbladderthree located at the ear lobe (Figure 3). 27 The utilization of functional magnetic resonance imaging (fMRI), as employed by Romoli et al to investigate brain stem auricular acupoint (BSAA), has demonstrated the potential to investigate other auricular points on the outer ear, such as the tragus, antitragus, and ear lobe.…”
Section: Evaluation Of Dp From the Perspective Of The Chinese Auricul...mentioning
confidence: 99%
“…또한, GV20(百會), PC6(內關) 등 혈위 에 대한 침 자극은 항진된 교감신경계의 활성을 줄 이고 중추신경계의 norepinephrine 분비를 줄이는 작 용을 하며, 뇌내 gamma-aminobutyric acid(GABA) 수치를 높이는 등의 작용으로 불면에 효과가 있다 19 . 두통의 침 치료에 관한 연구에서는 EX-HN5(太陽), GB20(風池), TE17(翳風), 등 혈위가 두통과 관련한 통증 유발점(trigger point)과 연관이 있어 이들 혈위 에 대한 침 치료가 관자근(temporalis muscle), 등세 모근(trapezius muscle), 목빗근(sternocleidomastoid muscle) 등 근육의 긴장을 줄여 두통을 해소할 수 있을 것으로 보았다 20…”
unclassified